Efficacy of ferric carboxymaltose for treatment of iron deficiency anemia diagnosed in the third trimester of pregnancy: A case–control study. Issue 4 (19th January 2023) - Busnelli, Andrea; Fabiani, Chiara; Acerboni, Stefano; Moretti Montefusco, Sarah; Di Simone, Nicoletta; Setti, Paolo Emanuele Levi; Bulfoni, Alessandro
Abstract: Aim: To assess the efficacy of intravenous ferric carboxymaltose (IV FCM) for the treatment of iron deficiency anemia (IDA) diagnosed de novo in the third trimester of pregnancy. Methods: Case–control study conducted in pregnant women with IDA newly diagnosed in the third trimester of pregnancy. Women treated with a single IV FCM injection were included as cases and those who received daily 210 g of oral ferrous sulphate (FS) as controls. Controls were matched to cases in a 2:1 ratio by basal hemoglobin (Hb) concentration (±0.5 g/dl). Results: A total of 35 cases and 70 controls were included in the study. The mean Hb concentration level significantly increased after iron treatment in both cases (from 9.3 ± 0.8 to 11.1 ± 0.8 g/dl, p  < 0.0001) and controls (from 9.6 ± 0.9 to 10.9 ± 1 g/dl, p  < 0.0001). The rate of women who exceeded the recommended threshold of 11 g/dl after treatment did not significantly differ between cases (63% (95%CI, 45%–79%)) and controls (56% (95%CI, 44%–68%)) ( p  = 0.48). Comparison of maternal and neonatal outcomes and adverse effects did not show any significant difference between groups. Conclusions: Our results suggest that IV FCM and oral FS can be considered equally effective in the treatment of IDA newly detected in the third trimester of pregnancy.